Ability to Understand Mathematical Concepts and Adversity Quotient Students Reviewed from Al-Qur’an Memorize Ability - Elma Triana; Lisa Dwi Afri (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2023)
Students often find it difficult to understand the concepts in mathematics. Most of them find it difficult to concentrate and give up easily on understanding math concepts. Regarding this, the adversity quotient is very necessary for students. The adversity quotient is a student's internal factor in the form of persistence, responsibility, control, and views on dealing with problems. Memorizing the Qur'an is known to train a person to maintain peace of mind, concentrate easily, and control the emotions that exist within. The purpose of this research is to describe the ability to understand mathematical concepts and the adversity quotient of students in terms of their ability to memorize the Al-Qur'an. This research is a quantitative descriptive study with research subjects, namely class VIII students one of SMP Private at Binjai. Data collection techniques in this study used questionnaires, documentation, and interviews. Data analysis was carried out using descriptive statistics, namely narrating and describing the results of questionnaires and interviews. The results showed that the ability to understand mathematical concepts and the adversity quotient were influenced by memorizing the Qur'an. Religious subjects (SR) have the ability to understand high-level mathematical concepts and the adversity quotient of the climbers group. Superior Subjects (SU) have the ability to understand intermediate-level mathematical concepts and the adversity quotient of the camper group. Elementary Subjects (SD) have the ability to understand low-level mathematical concepts and the adversity quotient of the quitters group.